Optical microrheology measurements for determination of sol-gel transitions of chitosan hydrogels - Domagalski, P; Orczykowska, M; Owczarz, P; Dziubinski, M (Journal of physics. Conference series, 2015)
The combination of medicinal substance and an appropriate polymer matrix with specially adjusted permeability has became a basic form of medicine in the controlled drag delivery. One of main solutions used recently in pharmacology is the application of polymer matrices which form colloidal systems. The sol-gel phase transition is inhibited by a change of pH or temperature. Thermosensitive systems are produced from polymers whose sol-gel transition in water solutions depends on temperature. Thermosensitive hydrogel systems are currently obtained mainly from poly(N-isopropylacrylamide) (PNIPA), copolymer (polyethylene oxide - polypropylene oxide - polyethylene oxide), polyethylene glycol, lactic acid copolymer with glycolic acid and polyethylene glycol, and polysaccharides (xyloglucane, ethylcellulose, hydroxyethylcellulose and chitosan). At the temperature below 25°C these systems occur in the form of sols which at human body temperature are transformed into gels. Such systems belong to the so called intelligent ones and are a subject of special interest, particularly in view of their possible use as drug carriers and also as material for cell culture in the past.